Impact of the teach-back method on caregiver outcomes using the “Timing it Right” framework for hemodialysis patients - Huang, Jing; Lin, Xiutian; Xiong, Dailan; Huang, Kaiwei; Luo, Xiaofei; Lin, Qinwen; Li, Min; Zhang, Ping (Frontiers in Public Health, 2023)
Background The caregivers play vital roles in the health care of hemodialysis patients. Ineffective education strategy for the caregivers negatively affects the care ability of caregivers. This study aimed to evaluate the effectiveness of the teach-back method based on the “Timing it Right” framework on the caregivers’ care ability, emotions and health-related quality of life for hemodialysis patients. Methods The study involved 78 caregivers of 78 hemodialysis patients. Participants in the control group received routine nursing care and traditional oral health education, while those in the intervention group received health education through the teach-back method based on the “Timing it Right” framework. All participants were followed for 6 months. The degree of anxiety and depression of caregivers was evaluated through the Self-rating Anxiety Scale (SAS) and Self-Rating Depression Scale (SDS), respectively. The care ability of caregivers was assessed by the Family Caregiver Task Inventory (FCTI). The health-related quality of life of hemodialysis patients was evaluated using the 36-item Short Form Health Survey (SF-36). Results Compared to baseline (T0), the SAS, SDS and FCTI scores of the intervention group were significantly reduced at the time of discharge (T1), three (T2) and 6 months (T3) (all p < 0.001). Besides, at T1, T2, and T3, the FCTI scores of the intervention group were significantly lower than that in control group (all p < 0.001). The SAS and SDS scores were also significantly lower in the intervention group at T1, T2, and T3 compared to the control group (all p < 0.001). For SF-36 scores, all domains of the intervention group were significantly higher than those of the control group at T1, T2 and T3, including physical functioning (p < 0.001), role physical (p = 0.007), bodily pain (p < 0.001), general health (p = 0.002), vitality (p = 0.043), social functioning (p = 0.016), role emotional (p = 0.002), and mental health(p = 0.025). Conclusion The application of teach-back method based on the “Timing it Right” framework could obviously alleviate the anxiety and depression of caregivers for hemodialysis patients. Furthermore, it could significantly improve the care ability of caregivers and the quality of life of patients.